2008
DOI: 10.1590/s0100-83582008000400016
|View full text |Cite
|
Sign up to set email alerts
|

Manejo químico de plantas daninhas na cultura do milho em função de características morfofisiológicas e redução de espaçamento da cultura

Abstract: RESUMO -Objetivou-se com este trabalho avaliar o efeito da integração de redução de espaçamento entre linhas sobre características morfofisiológicas de híbridos e estratégias de manejo químico de plantas daninhas em milho. O experimento foi realizado a campo, em delineamento de blocos casualizados, com quatro repetições, em um fatorial 2 x 2 x 5, em que o primeiro fator representou os híbridos de milho (Sprint, ciclo superprecoce e folhas mais eretas, e Penta, ciclo precoce e folhas mais planas); o segundo, es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
5

Year Published

2009
2009
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 19 publications
0
6
0
5
Order By: Relevance
“…The highest yield was obtained with the hybrid XB 7253 with 70,000 plants ha -1 in the spacings of 0.45 and 0.90 m, while for the hybrids XB 6010, XB 6012 and XB 9003 there was no significant response to spatial arrangements and 50,000 plants ha -1 could be recommended for both spacings. In another study, Trezzi et al (2008) found higher yield with the hybrid Penta in the spacing 0.90 m, while the hybrid Sprint had similar yield in both spacings 0.90 m and 0.45 m.…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…The highest yield was obtained with the hybrid XB 7253 with 70,000 plants ha -1 in the spacings of 0.45 and 0.90 m, while for the hybrids XB 6010, XB 6012 and XB 9003 there was no significant response to spatial arrangements and 50,000 plants ha -1 could be recommended for both spacings. In another study, Trezzi et al (2008) found higher yield with the hybrid Penta in the spacing 0.90 m, while the hybrid Sprint had similar yield in both spacings 0.90 m and 0.45 m.…”
Section: Resultsmentioning
confidence: 86%
“…However, the increase in N rates requires the split of nitrogen fertilization to enhance the increase in yield (Von Pinho et al, 2008). The use of higher nitrogen rates, adequate plant density and sowing speed may increase the corn yield without changing the spacing between lines (Alvarez et al, 2006;Trezzi et al, 2008;Alvarez et al, 2009;Kappes et al, 2011;Sangoi et al, 2011). The reduction in spacing requires suitable platforms for harvesting, therefore the farmer needs to modify or acquire new platforms to harvest in reduced spacings , which results in increased costs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tabela 2 -Síntese da análise de variância e do teste de médias para as variáveis número de fileiras por espiga, número de grãos por fileira, número de espigas por planta, peso de mil grãos (g) e produtividade (kg ha -1 ) de três híbridos de milho submetidos a três espaçamentos NUNES, 1995;TREZZI et al, 2008). Esses resultados existentes na literatura podem ser atribuídos a diversos fatores, entre os quais se pode citar o tipo de híbrido, população de plantas, as características climáticas da região e o nível de fertilidade do solo, dentre outros (SANGOI et al, 2002).…”
Section: Desempenho De Híbridos De Milho Na Região Sudoeste Do Paranáunclassified
“…Several studies have demonstrated the interference of plants in corn crops (Borghi et al, 2008;Freitas et al, 2008;Trezzi et al, 2008). In the Northeastern region of Brazil, weed control is performed mainly with a hoe, but in large agricultural companies, herbicides are frequently used.…”
Section: Introductionmentioning
confidence: 99%